Studies in Intra-Africa Relations: Nigeria-South Africa Cooperation (1994-2015) - Oluwadara, Deborah Ebunoluwa; Adesegun, Abiodun A. (NIU Journal of Humanities; Vol 7 No 2 (2022): NIU Journal of Humanities, Vol. 7 No. 2, June 2022DO - 10.58709/niujhu.v7i2.1468, 2022)
Nigeria and South Africa are big hegemons in Africa. In spite of their current rivalry on the international arena, especially for a permanent seat in the United Nations Security Council, there is more that brings the two countries together than separates them. Nigeriaâ€™s anti-apartheid policy only lasted as long as the apartheid regime in South Africa. Upon the abandonment of the racist regime in South Africa, Nigeria was more than willing to pursue warm relations with the South African government. With sufficient pressure mounted on South Africa and the rest of the International Community, the apartheid regime collapsed in South Africa in 1994. Nigeria, like other countries, then began a policy of political and economic engagements with South Africa from 1994 onwards. In spite of the fact that there are regional economic blocs in Africa, economic cooperation among African countries has not always been easy. One reason that may account for the situation is that economic factors are often linked to the political, socio-cultural and military aspects of nation building. This study investigated the origins and nature of their political, economic and socio-cultural relationship to ascertain whether this can be a template for economic cooperation among African countries. This study made use of secondary sources of data such as books, journals, articles, previous related research works from libraries and Internet sources. This study adopted a qualitative approach. Therefore, deductive analysis method   was employed. This research has found that despite the fact that the Nigeria-South Africa cooperation is less than perfect as it has its many short comings; it is still an acceptable template for intra-Africa co-operation. Keywords: Bi-lateral relations, Competition, Co-operation, Hegemony.